Plan de ventas para mejorar la comercialización a partir del proceso de ventas en la empresa STHOPA INVERSIONES E.I.R.L, periodo 2021 - Araujo Panduro, José Luis (2023)
Currently There is a great demand for natural products derived from plants. This city of Iquitos and in turn in the province of Maynas, Loreto Region, which are used for various culinary activities such as restaurants, homes, among others, this makes the Company. STHOPA INVERSIONES can make the most of this situation in the country. The company has a sales deficit due to poor organization, lack of resources, lack of, delegation of functions, responsibilities and lack of knowledge to work as a team. A group of consumers who are customers of the company will be tested, Identify A problematic factor for the sales department. The title of the thesis project is Sales. Planning for Marketing Improvement. The title of the thesis project is "Sales Planning Improve Marketing from the Sales Process in the Company STHOPA Inversiones eirl," Shows all the weaknesses of the company's sales department, which does not have a well-structured function. Sales planning will be based on a review of each consultant's work to determine the best option. The Sales Plan will be carried out according to the studies carried out by the sales worker, to determine what is most appropriate for the company, or the correct thing, if they are taking advantage of the total hours of work and to know if the resources that are being used are being wasted. have.